Youth mental ill health and secondary school completion in Australia: time to act. Issue 4 (6th July 2016) - Bowman, Siann; McKinstry, Carol; McGorry, Patrick
Abstract: Aim: This paper reviews the evidence of youth mental ill health and its impact on secondary school educational attainment. Methods: This narrative review presents the current research related to the mental ill health of young people in urban and rural Australia, their educational attainment and the effectiveness of mental health strategies implemented in secondary schools. Results: The prevalence of mental ill health is high for Australian young people and the onset of depression, anxiety, substance‐use disorders and first episode psychosis (FEP) commonly occurs when the individual is at school. The prevalence is reported to be higher for rural young people and barriers to treatment exist. Current evidence suggests that 40% of young people experiencing depression or anxiety disorders are not completing secondary school. Further evidence shows that over 50% of individuals who experience FEP do not finish secondary school. Current mental health promotion strategies employed in secondary schools have not been shown to reduce rates of depression or anxiety in adolescence nor identify prodromal or acute FEP. These strategies have not led to interventions that assist young people with mental ill health to finish school. Conclusions: Not completing secondary school can limit employment options, lead to severe levels of disadvantage and increased burden on welfare and healthcare systems. All young people, including those in rural areas, have the right to education and should not be disadvantaged in their educational aspirations because they have an emerging or current mental illness.